Evaluation Analysis of Islamic Religious Education Curriculum at Madrasah Tsanawiyah Ar Ruhama Kuningan - Abas, Saehu; Mabrur, Hajjin; Muhaimin, Aghust; Syauqi, Muhammad; Ubaidillah, Muh. Luthfi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This study aims to evaluate the curriculum of Islamic Religious Education (PAI) subjects with the EKOP (Evaluation of Instructional Quality and Output) evaluation model. The method used in this study is qualitative. Data was collected by conducting observations, interviews with the vice principal of the madrasah for curriculum, two Islamic Religious Education teachers, and students. Other data are documentation data in the form of assessment documents of Islamic Religious Education teachers at Madrasah Tsanawiyah (MTs) Ar Ruhama Kuningan. The results of this study prove that the curriculum evaluation with the EKOP model on the aspects of the quality of the learning process and output. The results of the evaluation indicate that the quality of the curriculum is categorized as good. The indicators are teacher performance regarding mastery of learning materials, understanding student characteristics, learning management, student guidance, and assessment. The learning is also categorized as very good because most students' learning activities and motivation are very good, so their academic achievements can meet learning objectives. Therefore, the results of this study conclude that excellent and practical curriculum evaluation positively affects the quality of learning and meets the six scopes of assessment aspects.